Corruption and the Development of Small- and Medium-Sized Enterprises (SMEs) in Vietnam - Nguyen Thanh, Nguyen (Archives of Business Research, 2021)
This document studies the nature of corruption in Vietnam and its impact on the development of SMEs. The author surveyed the experience of SMEs’ leaders on corruption and their perception about the impact of such dishonest behavior on the development of their firms. One thousand two hundred questionnaires were distributed by mail resulting in 612 usable responses. Traffic police, taxation, and customs are considered as most corrupt. Besides, 81.7% of enterprises say there is no effect on corruption to their business, 10.5% conclude it is positive, but only 7.8% see corruption as a constraint on their firm’s performance. The results provide that there is no relationship between corruption to enterprises’ development and prove local SMEs can adapt to this environment.